Sebuah Potensi Kultur Sekolah Dalam Penguatan Nilai Pendidikan Tat Twam Asi Di SMA Negeri 1 Marga Kabupaten Tabanan: Potensi Kultur Sekolah Dalam Penguatan Nilai Pendidikan Tat Twam Asi Di SMA Negeri 1 Marga Kabupaten Tabanan - Ariasih, Ni Putu Devi Utami; Nanduq, Ferdinandus; Karsana, I Nengah (UHN IGB Sugriwa Denpasar, 2024)
School culture is a culture that is owned by every school and has its own characteristics, school culture is very important to do to strengthen the value of twam ation education and noble character of students, so as to create a young generation of noble character and noble character. Therefore, this study aims to (1) find out the potential form of school culture in strengthening the value of tat twam asi education at SMAN 1 Marga, Tabanan Regency, (2) find out the steps taken in strengthening the value of tat twam asi education at SMAN 1 Marga, (3) find out the educational value of tat twam asi what is contained in the school culture at SMAN 1 Marga. The theory used is Cultural Structuralism from Yasraf 2002, Consensus from Durkheim 1990 and Values from Adisusilo 2013. The subjects of this study were the Principal, Hindu Religion Teacher, BK Teacher, Vice Head of Student Affairs, Head of TU, Parents of Students and Students at SMAN 1 Marga. The method used is Observation, Interview, Documentation, and Literature Study. The data that has been collected was analyzed using a qualitative descriptive analysis method with steps of data reduction, data presentation, and drawing conclusions.The results of research and discussion in this study 1) Forms of School Culture Potential in Strengthening Tat Twam Asi Educational Values at SMAN 1 Marga: School social climate, School Intellectual Climate, Rules and Policies, Traditions and Routines, Structure, Effective Partnering, Norms. 2) Ste ps Taken in Strengthening Tat Twam Asi Educational Values at SMAN 1 Marga: Strengthening tat twam asi teachings, Throug extracurricular, discussions and making mutual agreements, religious activities, distribution of coordinators in each activity, communicating with parents of students, and implement and implement. 3) The Value of Tat Twam Asi Education in SMAN 1 Marga: Mutual Cooperation and ToleranceKeywords: School Culture, Strengthening Tat Twam Asi